A Note on Free Module Decomposition over A Principal Ideal Domain - Ni Wayan Switrayni; I Gede Adhitya Wisnu Wisnu Wardhana; Qurratul Aini (IndoMS, 2023)
Some methods have been used to express a finitely generated module over a principal ideal domain as a finite direct sum of its cyclic submodules. In this paper, we give an alternative technique to decompose a free module with finite rank over a principal ideal domain using eigen spaces of its endomorphism ring.